OP0195 Role of seropositivity on mortality in ra and the impact of treatment with dmards. (12th June 2018) - Alemao, E.; Guo, Z.; Weinblatt, M.E.; Shadick, N.A.
Abstract : Background: Previous studies showed that RF positivity (+) in RA was associated with increased overall mortality, and that cause-specific mortality rates differed by autoantibodies. Anti-citrullinated protein antibodies (ACPAs) have been associated with cardiovascular death, and RF with death due to neoplasm and respiratory disease. 1 Objectives: To evaluate the association of serostatus (in particular, antibody [Ab] titres) with mortality and its modification by DMARDs. Methods: Administrative claims data from Optum Clinformatics Data Mart and Humana databases (2006–2016) were used. Inclusion criteria: 2 diagnosis codes for RA plus 1 DMARD prescription; age ≥18 years (y);≥6 months (M) baseline (BL;+/–3 M from index date). Index date was the first test date for ACPA or RF (main analysis) or the DMARD prescription date (DMARD effect on mortality analysis). Patients (pts) with ankylosing spondylitis, Crohn's disease, lupus, psoriatic arthritis or ulcerative colitis at/before index date were excluded. Based on BL Ab test, pts were categorised into Ab status of ACPA+/–, RF +/–and double +/–. Ab +pts were then categorised into 2 groups based on Ab titres. DMARD-exposed pts were categorised into biologic (b)DMARD (use of any bDMARD) and conventional (c)DMARD (use of a cDMARD but never a bDMARD) cohorts. Crude mortality rates per 1000 pt-y, as well as adjusted analysis using traditional multivariate regression and disease risk score methods, were used. Covariates were age, sex, region, physician office visits in past 3 M, indicator variable for RA diagnosis before ACPA/RF testing, past hospitalisation, medication use (steroids, NSAIDs, salicylates), DMARD use and co-morbidities. Results: A total of 53 849 and 79 926 pts with RA had evaluable ACPA and RF status, respectively. The average (SD) age was 61.4 (15.2) and 61.8 (15.6) y in the ACPA and RF cohorts, respectively. For both ACPA and RF, mortality rates were significantly higher in Ab +vs Ab– pts, and were highest in pts with the highest Ab titres (table 1). The hazard ratios (HRs) for mortality were highest in pts with double positivity (figure 1A). HRs were higher in Ab +vs Ab– pts exposed to cDMARDs. There was no difference in mortality between Ab +vs Ab– pts in the bDMARD-exposed group (figure 1B). Conclusions: Elevated ACPA and RF titres were independently associated with increased mortality among pts with RA. The associations between ACPA/RF and mortality persisted in those treated with cDMARDs but not with bDMARDs. Further studies are warranted to evaluate the effect of bDMARDs on mortality in seropositive pts. Reference: [1] Ajeganova S, et al. Ann Rheum Dis2016;75:1924–32. Disclosure of Interest: E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Z. Guo Employee of: Bristol-Myers Squibb, M. Weinblatt Grant/research support from: Amgen, Bristol-Myers Squibb, Crescendo Bioscience, Sanofi, Consultant for: Amgen, Bristol-Myers Squibb, Crescendo Bioscience, AbbVie, Lilly, Pfizer, Roche, Merck, Samsung Novartis, N. Shadick Grant/research support from: BRASS registry, Amgen, Bristol-Myers Squibb, and Mallinckrodt, Consultant for: Bristol-Myers Squibb